SAVE CLIENT IN SERVICE - Shukurov I.X (EPRA International Journal of Economic Growth and Environmental Issues(EGEI), 2022)
The article describes in detail the problem of service and how to serve the customer, how to retain the customer, how the employees behave in front of the customer, everything is written in detail.